Idiopathic multicentric Castleman disease in children: a single-center retrospective analysis - Junye Du; Jiafeng Yao; Honghao Ma; Li Li; Ang Wei; Liping Zhang; Dong Wang; Zhigang Li; Rui Zhang; Tianyou Wang (BMC Pediatrics)
Abstract Objective To investigate the clinical features, pathological phenotype, treatment and prognosis of idiopathic multicenter Castleman disease (iMCD)in children. Methods From January 2017 to September 2023, basic information, laboratory tests, treatment and prognosis of children diagnosed with iMCD who attended Beijing Children's Hospital of Capital Medical University were collected. Results A total of 9 children were enrolled, with a median age of onset of median 11 (2–15) years, 6 males and 3 female. 3 cases were pathologically typed as plasma cell type, 1 case was mixed type, and the remaining 5 cases were hyaline vascular type. 9 children received different regimens of chemotherapy. The median follow-up time was 26 (13, 58) months, with no deaths, 7/9 cases showing improvement, 1/9 cases showing stable condition, and 1/9 cases showing active condition. Conclusion Children with multicentric CD often have systemic symptoms, lymph node enlargement and related compression symptoms are the most common manifestations, followed by fever, malaise and other systemic symptoms. Anti-IL-6-based therapy combined with hormones lenalidomide and other medications have a specific therapeutic effect on multicentric CD.